2016
DOI: 10.11648/j.sjph.20160401.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of National Health Insurance Holding on the Choice of Health Facility for Childbirth in Ghana

Abstract: Maternal and child mortalities are among major health problems facing developing countries such as Ghana. Most of these deaths can be avoided by utilization of maternity health care services. The study examines the effect of health insurance holding and other socioeconomic and demographic factors on the choice of health facility for childbirth in Ghana. The study used data from the 2008 Ghana Demographic and Health survey. Data were analyzed for descriptive statistics as well as a Multinomial Logistic Regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The odds of delivery at health facility among mothers who had the number of living children 2-4 were reduced by 52% as compared to those who had only one child. This nding is consistent with the study conducted in Pakistan and Rural Tanzania, This is due to that Women who deliver their rst child without any problem might think that they will not face the di culty of delivering their second baby and they may not also found a person who cares for their rst child to leave him at home while they go to the health institution for delivery [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 84%
“…The odds of delivery at health facility among mothers who had the number of living children 2-4 were reduced by 52% as compared to those who had only one child. This nding is consistent with the study conducted in Pakistan and Rural Tanzania, This is due to that Women who deliver their rst child without any problem might think that they will not face the di culty of delivering their second baby and they may not also found a person who cares for their rst child to leave him at home while they go to the health institution for delivery [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 84%
“…The result is in line with previous studies. [11][12][13] Health insurance can overcome financial barrier that plays an important role in access to maternal health services. 10 The increase in institutional delivery through health insurance becomes important, considering that delivery at health facilities plays an important role to reduce maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…10 The review was also supported by recent studies. [11][12][13] In Ghana, health insurance increases institutional delivery by 32.3%. 11 Another study also found that health insurance was a significant factor de-termining delivery at public health facilities and the ownership of health insurance during pregnancy tends to increase 2.5 times to deliver at health facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is finding is consistent with the study conducted in Pakistan and Rural Tanzania. e reason is that women who deliver their first child without any problem might think that they will not face difficulty in delivering their second baby and they may not also find a person who cares for their first child at home while they are at the health institution for delivery [21,[27][28][29][30][31][32][33][34][35][36]. Communities with a high proportion of educated women had a 70% higher chance of institutional delivery as compared to communities with a low proportion of educated women.…”
Section: Discussionmentioning
confidence: 99%